2019
DOI: 10.1152/ajprenal.00366.2019
|View full text |Cite
|
Sign up to set email alerts
|

Capillary rarefaction is more closely associated with CKD progression after cisplatin, rhabdomyolysis, and ischemia-reperfusion-induced AKI than renal fibrosis

Abstract: Acute kidney injury (AKI) is a strong independent predictor of mortality and often results in incomplete recovery of renal function, leading to progressive chronic kidney disease (CKD). Many clinical trials have been conducted on the basis of promising preclinical data, but no therapeutic interventions have been shown to improve long-term outcomes after AKI. This is partly due to the failure of preclinical studies to accurately model clinically relevant injury and long-term outcomes on CKD progression. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 76 publications
4
41
0
Order By: Relevance
“…Under this circumstance, CKD progression is associated with impaired tubular regeneration, endothelial dysfunction and prolonged hypoxia, persistent inflammation, interstitial fibrosis, epigenetic alteration, activated renin-angiotensin-aldosterone-system (RAAS), mitochondrial dysfunction, and cellular senescence [ 141 , 142 , 143 , 144 ]. Some of these changes have been reported in cisplatin-induced CKD [ 9 , 135 , 145 , 146 , 147 , 148 ].…”
Section: Cisplatin-induced Nephrotoxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Under this circumstance, CKD progression is associated with impaired tubular regeneration, endothelial dysfunction and prolonged hypoxia, persistent inflammation, interstitial fibrosis, epigenetic alteration, activated renin-angiotensin-aldosterone-system (RAAS), mitochondrial dysfunction, and cellular senescence [ 141 , 142 , 143 , 144 ]. Some of these changes have been reported in cisplatin-induced CKD [ 9 , 135 , 145 , 146 , 147 , 148 ].…”
Section: Cisplatin-induced Nephrotoxicitymentioning
confidence: 99%
“…Chronic hypoxia is considered as a common pathological condition in CKD [ 10 , 163 ]. Though studies have revealed that multiple pathophysiological mechanisms are related to cisplatin-induced AKI to CKD progression [ 9 , 135 , 145 , 146 , 147 , 148 ], the investigation focusing on the role of HIF in this field is lacking. Nevertheless, HIF is a potential player in this process because of its essential role in hypoxia and its interactions with multiple pathophysiological procedures involved in the progression of CKD ( Figure 2 ).…”
Section: Hif In Cisplatin-induced Aki To Ckd Progressionmentioning
confidence: 99%
“…Previous studies reported the use of these nanoparticles for BV assessment in both rat and mouse models, as well as their application to patients with CKD [64][65][66]. In this context, a recent experimental study has shown that capillary rarefaction is more closely associated with AKI-to-CKD progression than renal fibrosis [67]. This imaging technique may be effectively used for assessing AKI-to-CKD progression and for tracking and monitoring the distribution of specific cells (e.g., mesenchymal stem cells) in the AKI setting [68].…”
Section: Dynamic Contrast-enhanced Mrimentioning
confidence: 99%
“…The renal capillary network was often destroyed during non-septic AKI [33], and angiogenesis was indispensable for efficient tubular recovery [34,35]. In septic AKI, microcirculation failure, rather than histological capillary destruction, caused changes in the oxygen supply to the tubules.…”
Section: Microcirculation Failurementioning
confidence: 99%